Nonorthogonal tight-binding model with H–C–N–O parameterisation. Issue 4 (3rd March 2016) - Maslov, Mikhail M.; Podlivaev, Alexei I.; Katin, Konstantin P.
Abstract : A parametric nonorthogonal tight-binding model (NTBM1) with the set of parameters for H–C–N–O systems is presented. This model compares well with widely used semi-empirical AM1 and PM3/PM7 models but contains less fitting parameters per atom. All NTBM1 parameters are derived based on a criterion of the best agreement between the calculated and experimental values of bond lengths, valence angles and binding energies for various H–C–N–O molecules. Results for more than 200 chemical compounds are reported. Parameters are currently available for hydrogen, carbon, nitrogen, oxygen atoms and corresponding interatomic interactions. The model has a good transferability and can be used for both relaxation of large molecular systems (e.g., high-molecular compounds or covalent cluster complexes) and long-timescale molecular dynamics simulation (e.g., modelling of thermal decomposition processes). The program package based on this model is available for download at no cost fromhttp://ntbm.info .